Distribution of chemical elements in river sediments and alluvial soils from the Strumica River basin, North Macedonia - Stafilov, Trajče; Šajn, Robert; Trajanova, Katerina (Macedonian Journal of Ecology and Environment, 2024)
The distribution of 20 chemical elements (Ag, Al, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, P, Pb, Sr, V and Zn) in river sediments and alluvial soils from the Strumica River basin in North Macedonia is presented. A total of 12 sediment and 24 soil samples were collected, from four locations of the Strumica River and eight locations of its main tributaries (Bansko, Dabile, Turija, Vodoča, Radoviška River and Injevska River). The content of the analysed elements was determined using inductively coupled plasma - atomic emission spectrometry (ICP-AES). All data obtained for the analysed samples were statistically processed using Stat Soft 11.0 software, whereby a descriptive statistical analysis of the element content values was performed. The maps of the spatial distribution of the content for each element with a minimum and maximum value of the content for each element were also created. The matrix of correlation coefficient for the sediments and soil samples from the entire study area shows that there is a strong correlation between the contents of the elements: V-Fe (0.97), V-Cr (0.94), Fe-Cr (0.91), Mn-Fe (0.85), Sr-Ba (0.83), Mg-Ca (0.83), Mg-Li (0.82), Ni-Cr (0.81) and P-Sr (0.80). There are three factors in the matrix of loading factors for the elements in the sediment and soil samples. Factor 1 includes the chemical elements V, Cr, Ge, P, Cu, Ni and Pb, Factor 2 comprises the chemical elements Sr, Ba, Al, Zn and Mn and Factor 3 includes Mg, Li and Ca. The comparative statistics using three methods [t-test, F-ratio and R(T/B)] showed no difference between the distribution of the different chemical elements in the topsoil and subsoil samples. The results obtained show that the content of potentially toxic elements in the river sediments and alluvial soil is low and it can be concluded that the Strumica catchment is not polluted with heavy metals.